Visualization of the state of radiological contamination of food products - Kvasnikov, Volodymyr; Matviyenko, Dmitry (Technology audit and production reserves, 2018)
The object of research is the measurement, assessment, visualization and control of the effects of radiation exposure on life, public health, environmental protection and safety of national economic facilities, taking into account the risk of man-made disasters. One of the biggest problems is the need to develop scientific methods for the study of integrated assessments of the impact of man-made pressures on the environment and humans. And also in the creation of specialized systems for collecting, storing, processing and visualizing information using modern GIS (geographic information systems) technologies. This allows to analyze multidimensional data using their display while preserving the structural features of the information. Comprehensive assessment of the impact of man-made pollution is used, which is a necessary condition for metrological support for in-depth study of the structure of the system, as the unity of components and connections. As a result of this work, a specialized system for analyzing the data obtained when measuring samples of food products for compliance with the standards for a particular product has been formed. The basis of this system is the development of a database of food monitoring in the Cherkasy region (Ukraine), the structure of which includes a central bank and 5 specialized units. Examples are given of the calculation of comparative assessments of the state of areas of the region, including the radiation component. Measurement and obtained control over a complex situation with simultaneous consideration of a large number of heterogeneous parameters are carried out. This is due to the fact that the proposed method complements the well-known methods of mathematical modeling of radiological contamination, directly affect the quality of life of the population, and has several features. In particular, the development of a software environment for the construction and visualization in the form of thematic maps of the correlation between radiological contamination and the incidence of the population of the region. This ensures the possibility of obtaining an assessment of the risk degree to public health and making informed decisions to minimize it.